Perhubungan antara gaya kepimpinan penyertaan dalam pengurusan kualiti menyeluruh dan prestasi kerja :peranan tanggapan penghargaan sebagai pembolehubah moderator - Mohamed Fadzil, Abdul Razab. (Universiti Malaysia Sarawak, UNIMAS, 2008)
This paper examines the relationship between leadership in Total Quality Management , perceived organizational support and job performa nce. The data of this research is collected by interview approach and questionnaires forms. 100 completed survey questionnaires have been collected from the workers who have worked in Jabatan Kebajikan Masyarakat Negeri Sarawak. The outcomes of hypotheses testing using correlation analysis showed that there is significant relationship between participative leadership in TQM setting and job performance. The outcomes of hypotheses testing using hierarchical regression analysis showed that perceived organizat ional support as a moderator in the relationship between participative leadership in TQM setting and job performance.